Pengaturan Tentang Tanggung Jawab Pidana Pelaku Pengidap Gangguan Jiwa Yang Melakukan Tindak Pidana Pembunuhan (Tinjauan Terhadap Hukum Pidana Positif di Indonesia) - Annisa Hidayati (Yayasan Cendekia Gagayunan Indonesia, 2024)
In accordance with the principle of the rule of law, every person who commits a criminal offense must be held accountable. However, criminal law as stipulated in Article 44 paragraph (1) of the Criminal Code that a mentally disturbed person who commits the crime of murder is juridically normative to eliminate his guilt so that he is free from criminal responsibility. However, Article 44 paragraph (1) of the Criminal Code does not clearly define how a person with mental disorder actually is, and this problem requires legal certainty. Therefore, this study aims to determine the criteria for a person with mental disorder as referred to in Article 44 paragraph (1) of the Criminal Code and the responsibility of a person with mental disorder who commits the crime of murder. This research uses normative legal research, namely research on secondary data in the form of primary, secondary, and tertiary legal materials collected through literature studies. Then the legal materials are processed and analyzed descriptively qualitative. The results showed that Article 44 paragraph (1) of the Criminal Code does not clearly determine the criteria for a person suffering from mental disorders. Then in principle, a person with mental illness who commits the crime of murder cannot be held criminally responsible, because his guilt is forgiven according to Article 44 paragraph (1) of the Criminal Code.